Isomorphisms of AC(𝜎)-spaces - Doust, Ian; Leinert, Michael (Studia mathematica <Warszawa>, 2015)
Analogues of the classical Banach-Stone theorem for spaces of continuous functions are studied in the context of the spaces of absolutely continuous functions introduced by Ashton and Doust.